Climate Change and Human Well-Being Global Challenges and Opportunities - Weissbecker, Inka.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Although climate change is mainly caused in industrialized nations, the impact of climate change has spread across the globe, among developing countries and the world$1 (Bs most vulnerable populations. While the public health effects of environmental degradation and the resulting natural disasters are well-known, less is understood about their mental health impact and psychosocial well-being, and what types of interventions may best minimize the damage. Climate Change and Human Well-Being identifies the psychological responses and mental health impacts that accompany gradual environmental change and extreme weather events, and explains how climate change exacerbates existing inequities. Painstakingly researched, with extensive worldwide findings and instructive examples from the experiences of those affected by climate-change, this groundbreaking volume also examines the potential for collaboration among diverse sectors of society in responding to environmental crisis. Experts provide guidance for researchers, practitioners, policymakers, and the humanitarian aid community as they: Explain the relationship between environmental crisis, socioeconomic stressors, and psychological distress . Discuss the impact of acute and chronic extreme weather conditions on mental health and well-being. Analyze the short-and long-term effects of climate change on specific populations, and environmental refugees. Identify implications of climate change for peace, conflict, and stability. Demonstrate the importance of cultural competence in relief efforts. Include recommendations at the local, national, and global levels. Climate Change and Human Well-Being offers cross-cultural psychologists, psychiatrists, social workers, and professionals in related fields a greater understanding of complex issues, and new opportunities to engage in the emerging dialogue within and across the disciplines.s
Climate Change and Human Well-Being -- SECTION I: The Impact of Climate Change -- Gradual Environmental Changes -- Effects of Temperature and Heat Stress -- Extreme Weather-Related Events -- Social and Economic Stressors -- Climate Change Refugees and Internally Displaced Persons -- Climate Change and Human Security.-SECTION II. Specific Populations -- Women -- Children -- Individuals with Mental and Physical Disabilities -- SECTION III. Guidance and Recommendations -- Building Resilience -- Strengthening Local Capacity -- Responding to Humanitarian Crises -- Research and Evaluation.-. Conclusion.
Keywords: Philosophy (General).; Medicine; Applied psychology; Psychology; Cross Cultural Psychology; Medicine/Public Health, general